Update on Hearing Loss 2015
DOI: 10.5772/61217
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss and the Voice

Abstract: The voice varies according to the context of speech and to the physical and psychological conditions of the human being, and there is always a normal standard for the vocal output. Hearing loss can impair voce production, causing social, educational, and speech limitations, with specific deviation of the communication related to speech and voice. Usually, the voice is not the main focus of the speech-language pathology therapy with individuals with hearing loss, but its deviations can represent such a negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 60 publications
0
11
0
1
Order By: Relevance
“…Information regarding hearing ability would also be required to confirm the impact of hearing loss. HI is associated with hyperfunctional voice disorders in HI populations [56], as well as with pubophonic voice and diplophonia [55,56,57]. It is probable that HI contributed to M2's voice production in these tasks.…”
Section: Discussionmentioning
confidence: 98%
“…Information regarding hearing ability would also be required to confirm the impact of hearing loss. HI is associated with hyperfunctional voice disorders in HI populations [56], as well as with pubophonic voice and diplophonia [55,56,57]. It is probable that HI contributed to M2's voice production in these tasks.…”
Section: Discussionmentioning
confidence: 98%
“…Compression, gain settings, and signal processing in hearing aids may alter the auditory feedback of one's own voice in such a way that they impede adequate control of vocal intensity (Dillon, 2012b;Laugesen et al, 2011;Stenfelt, 2011). Based on previous research (Coelho et al, 2015), it is likely that the decreased auditory feedback resulting from an unaided hearing impairment also poses a challenge for controlling vocal intensity appropriately.…”
Section: Voice Intensity Controlmentioning
confidence: 99%
“…While the study of Laugesen et al (2011) resulted in a new tool for assessing the own-voice experience for hearing-aid users, the implications were somewhat limited, as the authors surveyed only the hearing-aid users at one point in time. Previous studies have suggested that hearing impairment complicates vocal regulation and is a potential risk factor for physiological voice problems (Coelho et al, 2015), which adds another layer of complexity.…”
mentioning
confidence: 99%
“…As a consequence of hearing impairment, speech and language skills tend to be either delayed or deviant depending upon several factors, such as type, degree, the onset of hearing loss, age at identification of deafness, and age at fitting appropriate amplification or implants. 4 - 6 Along with the deviancy, as mentioned earlier, due to lack of stimulation, the auditory feedback system loses the capability to regulate the voice characteristics. The vocal deviations that are prominently seen in individuals with hearing impairment include strain, breathiness, roughness, monotone, absence of rhythm, hoarseness, vocal fatigue, high pitch, reduced volume, and loudness with excessive variation; unbalanced resonance and imprecise articulation are essentially due to the lack of auditory monitoring of their own voice.…”
Section: Introductionmentioning
confidence: 98%